AI-Enhanced Risk Assessment in Physical Security Projects: An Applied Study to Improve Security Project Management (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study aims to investigate how AI methods can be used to improve risk assessment in the field of physical security. A quantitative approach was applied in this study, where data was collected from 160 individuals working in this sector, and their responses were processed and evaluated using modern statistical analysis techniques. The results showed that AI-enhanced risk assessment plays a crucial role in reducing human errors, as AI contributes to eliminating biases and shortcomings caused by human factors, which enhances the accuracy of predictions and the effectiveness of decisions taken in the context of risk management. The results revealed that AI increases the response of security teams to risks, by providing a comprehensive and in-depth analysis that enables them to take quick and intelligent measures based on actual facts, which enhances the efficiency of security operations. It has also been proven that the application of AI contributes to the development of security sustainability, as it enables continuous analysis and adjustment of security methods to suit changing threats. The study emphasizes the need to integrate AI into risk management strategies, which enhances the ability of organizations to successfully solve security problems and enhances long-term sustainability. The results highlight the need to enhance training and development for workers in this sector to ensure the best use of contemporary technology, which contributes to increasing the effectiveness and sustainability of physical security.
Keywords: Risk Assessment; Artificial Intelligence; Security Project Management; Physical Security; Risk Analysis; Performance Improvement; Security Applications